2010
DOI: 10.1002/hep.23292
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cell and Interleukin-12–Dependent Loss of Natural Killer T Cells in Hepatosteatosis

Abstract: Background Hepatosteatosis is associated with increased expression of tumor necrosis factor alpha (TNFα) and interleukin (IL)-12, major T helper (Th) 1 cytokines, and reduced hepatic NKT cell numbers. The relationship between lipid accumulation, cytokine expression, and hepatic NKT cells is not known. This study was conducted to assess the role of IL-12 in the development of hepatic steatosis and its potential impact on liver NKT cells. Methods Male C57Bl/6 wild type (Wt) and IL-12-deficient (IL12−/−) mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 42 publications
6
102
0
2
Order By: Relevance
“…The mechanisms underpinning the decrease in NKT cells in NAFLD are still unknown. Since IL-12 has been shown to increase NKT cell activationinduced cell death (52), abnormal Kupffer cell activation due to increased LPS, with consequent increase in IL-12, has been proposed to play a role (25). Additional studies should be performed to evaluate whether the reduction in CD3 + cells is specific for NKT or more generalized, and whether, on the contrary, a selective increase in intralobular CD3 + cells is associated with the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underpinning the decrease in NKT cells in NAFLD are still unknown. Since IL-12 has been shown to increase NKT cell activationinduced cell death (52), abnormal Kupffer cell activation due to increased LPS, with consequent increase in IL-12, has been proposed to play a role (25). Additional studies should be performed to evaluate whether the reduction in CD3 + cells is specific for NKT or more generalized, and whether, on the contrary, a selective increase in intralobular CD3 + cells is associated with the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between TLR-4 and endotoxin results in the release of a myriad of pro-inflammatory mediators which induce hepatic injury and fibrosis (24). Recently, Kremer et al (25) demonstrated that hepatosteatosis, in mice fed an MCD diet, is characterized at the hepatic level by an induction of interferon-γ and tumor necrosis factor-α, an elevated content of interleukin (IL)-12 and a remarkable reduction in the number and activity of NKT cells. The authors also highlighted that the reduction of the NKT cell population is due to the activation of Kupffer cells via an endotoxin-mediated mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Syn and Oo for their interest in our recently published article in HEPATOLOGY. 1 Our data show an inverse correlation with the accumulation of lipid and the relative proportions and function of hepatic natural killer T (NKT) cells. 1 The model used for our studies was intentionally simple, absent of significant inflammation or tissue injury, and human samples were selected to mimic this pathology.…”
mentioning
confidence: 74%
“…On observe par ailleurs un profil pro-inflammatoire des cellules NKT presentes (Li et al, 2005). Une etude recente a montre que, chez l'homme, la diminution du nombre de lymphocytes NKT est egalement correlee avec le degre de steatose (Kremer et al, 2010).…”
Section: Les Lymphocytes Nktunclassified